2019
DOI: 10.5530/ijper.53.2.37
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Synthesis, Characterization and Antimicrobial Evaluation of Novel Oxazolidinone- Biphenyl Chalcone Hybrid Derivatives

Abstract: Objective:The main objective of our present study, is to potentiate the antibacterial activity of biphenyl chalcones and oxazolidinones, thus in order to achieve the potent antibacterial agents, we coupled both derivatives by using green chemistry approach for Buchwald's protocol under ultrasound irradiation. Methodology: Ultrasonication technique was used to couple a series of 24 novel bromo-biphenyl-chalcone derivatives and 5-chloromethyl-oxazolidinone in the presence of copper iodide (CuI) (10 mol %) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Panigrahi et al coupled oxazolidinone and a biphenyl chalcone, which both have strong antibacterial activity, by using a green chemistry approach for Buchwald’s protocol under ultrasound irradiation and obtained a series of novel oxazolidinone–biphenyl chalcone hybrid derivatives (Figure ). In vitro antibacterial and antifungal activity studies showed that compared with the standard drugs ciprofloxacin and linezolid, compounds 7a – i showed significant antibacterial activity against both Gram-positive bacteria ( S. aureus , Bacillus subtilis ( B. subtilis ), and Streptococcus faecalis ( S. faecalis )) and Gram-negative bacteria ( Escherichia coli ( E. coli ), Klebsiella pneumoniae ( K. pneumoniae ), and Pseudomonas aeruginosa ( P. aeruginosa )) (MIC: 3.125–6.25 μg/mL). In the case of antifungal studies, compared with fluconazole (MIC: 6.25 μg/L against Candida albicans ( C. albicans ) and Aspergillus niger ( A. niger )), 7c – e exhibited medium potency against A. niger and C. albicans (MIC: 12.5 μg/mL).…”
Section: Structural Modification Of Oxazolidinone Drugs Based On Line...mentioning
confidence: 99%
See 1 more Smart Citation
“…Panigrahi et al coupled oxazolidinone and a biphenyl chalcone, which both have strong antibacterial activity, by using a green chemistry approach for Buchwald’s protocol under ultrasound irradiation and obtained a series of novel oxazolidinone–biphenyl chalcone hybrid derivatives (Figure ). In vitro antibacterial and antifungal activity studies showed that compared with the standard drugs ciprofloxacin and linezolid, compounds 7a – i showed significant antibacterial activity against both Gram-positive bacteria ( S. aureus , Bacillus subtilis ( B. subtilis ), and Streptococcus faecalis ( S. faecalis )) and Gram-negative bacteria ( Escherichia coli ( E. coli ), Klebsiella pneumoniae ( K. pneumoniae ), and Pseudomonas aeruginosa ( P. aeruginosa )) (MIC: 3.125–6.25 μg/mL). In the case of antifungal studies, compared with fluconazole (MIC: 6.25 μg/L against Candida albicans ( C. albicans ) and Aspergillus niger ( A. niger )), 7c – e exhibited medium potency against A. niger and C. albicans (MIC: 12.5 μg/mL).…”
Section: Structural Modification Of Oxazolidinone Drugs Based On Line...mentioning
confidence: 99%
“…Panigrahi et al coupled oxazolidinone and a biphenyl chalcone, which both have strong antibacterial activity, by using a green chemistry approach for Buchwald's protocol under ultrasound irradiation and obtained a series of novel oxazolidinone−biphenyl chalcone hybrid derivatives (Figure 7). 59 In vitro antibacterial and antifungal activity studies showed that compared with the standard drugs ciprofloxacin and linezolid, compounds 7a−i showed significant antibacterial activity against both Gram-positive bacteria (S. A systematic SAR study on screened compounds revealed that the effects of substitutions on ring R on the antibacterial potency were mainly steric; only the small or linear substituents (F < Cl < NO 2 OH < CH 3 < OCH 3 ) could be tolerated by the ribosomal binding site, whereas increases in the bulk of substituents were not tolerated. The results of this study may be able to guide researchers to further modify novel oxazolidinone−biphenyl chalcone hybrid derivatives and design more effective and selective antibacterial and antifungal agents.…”
Section: Structural Modification Of Oxazolidinone Drugs Based On Line...mentioning
confidence: 99%
“…Oxazolidinones incorporated with chalcone hybrids (12) were evaluated for in vitro antibacterial and antifungal activities by using the serial dilution method [16]. Results showed moderate antimicrobial activities as compared with the standard drugs ciprofloxacin and linezolid.…”
Section: Introductionmentioning
confidence: 99%